The grounding of pedagogical conditions of development of military special competence in officers-border guards during the master training - Veretilnik, Vitaliy; Didenko, Alexander (ScienceRise: Pedagogical Education, 2017)
The pedagogical conditions of the development of military-special competence of officers-border guards were discovered in the article. The topicality of the solution of problem of improvement of professional training of officers of border administration is caused by the series of factors, the one of which is a growth of the military component in professional activity of officers-border guards and also the difficult military-political situation in the East of Ukraine. The article grounds that the effectiveness of development of this competence during the master training will grow at the expanse of provision of the selection of content of the learning material in special disciplines taking into account the results of system analysis of the threats of border safety. The great importance is also inherent to the modeling and solution of practical situations of professional activity according to the problem principles. It is important for the formation and development of the officers’ abilities to making managerial decisions on organization of state border defense under special conditions and at special operations. The formation of communicative and pedagogical skills in officers on the base of andragogical model of interactive study is also the important pedagogical condition of the development of military-special competence of the officers of State border service of Ukraine. It is indicated by the results of analysis of scientific sources and the author’s experience. The solution of problem of the improvement of professional training of the officers of border administration depends on correct organization of their self-education. This process must be aimed at formation and development of the skills of work with different information sources, improvement of analytic and creative skills and increase of the level of masters’ independence